(untitled) (Journal of Nepal Physical Society, 2024)
This study explores the use of dielectric barrier discharge (DBD) atmospheric air plasma treatment to enhance the wicking properties of Nepalese Dhaka fabric. Plasma treatment significantly improved the fabric’s hydrophilicity, leading to a 1.14-fold increase in wicking coefficients compared to untreated fabric. These findings suggest promising applications for the plasma-treated fabric in sectors demanding enhanced moisture management and comfort, such as sportswear and general apparel. Moreover, the improved wicking properties make it suitable for the inner layer of medical garments like gowns and masks, where breathability, moisture management, and comfort are crucial. Understanding the effects of plasma treatment on Dhaka fabric’s properties is essential for optimizing its use in various industrial and consumer applications.